Pengaruh Abu Limbah Kulit Durian Sebagai Bahan Substitusi Semen pada Paving Block - Husna, Arifka Farah; Apriliawan, Vian Dito; Fauziyah, Shifa; Hartono, Hartono (Jurnal Proyek Teknik Sipil, 2024)
Paving block is a building material consisting of Portland cement, aggregate, water and additional materials. Paving blocks are used on sidewalks, driveways, parks, parking lots, as well as office and educational complexes. However, cracks and breaks are common, even in everyday use. The solution to increase the durability of paving blocks is to add durian peel ash to the mixture. The use of durian skin ash, apart from strengthening the material, also helps reduce the accumulation of waste in durian cultivation areas such as Gunungpati, where usually the durian skin is only burned, thereby accumulating rubbish which can pollute the environment and threaten health. Durian skin which is rich in silica, cellulose, lignin and low in starch can be used as a substitute for cement in making paving blocks. This research used an experimental method with compressive strength and absorption tests at various percentages of durian skin ash composition, namely 0%, 7%, 9%, 11% and 13%. The compressive strength results at 28 days with the optimum composition were obtained for durian skin ash of 9%, with a compressive strength value of 22.805 MPa and an absorption capacity of 5.030%.